The Proposal Preparation Program: A Group Mentoring, Faculty Development Model to Facilitate the Submission and Funding of NIH Grant Applications. (28th December 2021) - Weber-Main, Anne Marie; Thomas-Pollei, Kimberly A.; Grabowski, John; Steer, Clifford J.; Thuras, Paul D.; Kushner, Matt G.
Abstract : Supplemental Digital Content is available in the text. Abstract : This article describes the University of Minnesota Medical School Proposal Preparation Program (P3). P3 is designed to develop grant-writing skills for assistant professors preparing their first K- or R-series application to the National Institutes of Health (NIH). Three 4-month P3 cycles are conducted annually. For each cycle, a cohort of around 10 assistant professor participants and 5 regular faculty mentors meet for ten 2-hour group sessions. Participants receive iterative oral and written feedback on their proposals in development within a small, interdisciplinary, group mentoring setting providing structure, accountability, guidance, and support. Between sessions, 1 peer and 1 mentor are assigned (on a rotating basis) to critique each participant's developing application. The sessions include a brief mentor-led presentation on a particular grant section followed by discussion of each participant's application conducted by the assigned reviewers. The cycle concludes with a mock NIH review session, in which each participant is matched with a University of Minnesota faculty content expert who critiques their completed application using NIH guidelines. In a survey sent to all past P3 participants as of 2018 (n = 194), 88% of respondents reported having submitted their P3-developed NIH grant, and 35% of these submitters reported funding success. A separate analysis of institutional data for all past P3 participants as of 2016 (n = 165) showed that 73% submitted at least 1 NIH proposal since completing P3 and that 43% of these had acquired NIH funding, for a combined total of 193 million in funding awarded. The estimated rate at which participants obtained funding for their P3-developed grant application ( 35%) exceeds the national annual NIH grant funding rates ( 20%) by approximately 50%. This article provides the practical information needed for other institutions to implement a P3-like program and presents a cost–benefit analysis showing the advantages of doing so.